Thermal Absorption Performance Evaluation of Water-Based Nanofluids (CNTs, Cu, and Al2O3) for Solar Thermal Harvesting - Youngho Lee; Hyomin Jeong; Yonmo Sung (Energies, 2021)
For solar thermal harvesting, an experimental study was performed on the thermal absorption performance of water-based carbon nanotubes (CNTs), Cu, and Al2O3 nanofluids using a halogen lamp-based thermal radiation system. The effect of nanoparticle concentrations (0.01 wt.%, 0.1 wt.%, and 1 wt.%) on the nanofluid dispersion, stability, and thermal absorption characteristics was investigated, and a comparative analysis was performed for each type of nanofluid. All types of nanofluids increased the absorbance and electrical conductivity with increasing nanoparticle concentration, which contributed to improving the thermal absorption performance of nanofluids. The results showed that the thermal absorption performance was high in the order of carbon-based nanofluids (CNTs), metal-based nanofluids (Cu), and oxide-based nanofluids (Al2O3). In CNTs nanofluids, the thermal absorption performance expressed the time reduction rate, which was 12.8%, 16.3%, and 16.4% at 0.01 wt.%, 0.1 wt.%, and 1 wt.% test cases, respectively. Therefore, the 0.1 wt.%-CNTs nanofluid is more economical and appropriate. However, in Al2O3 nanofluids, the time reduction rate of the 1 wt.% nanofluid was significantly higher than that of the 0.01 wt.% and 0.1 wt.% nanofluids. In Cu nanofluids, unlike CNTs and Al2O3 nanofluids, the time reduction rate constantly increased as the nanoparticle concentration increased.